Intellectual Capital, Capital Structure, and CSR on Firm Value: The Moderating Role of Tax Avoidance - Amanda Aura Rosita; Acynthia Ayu Wilasittha (MAKSIMUM: Media Akuntansi Universitas Muhammadiyah Semarang, 2026)
This research assesses the influence of intellectual capital, capital structure, and CSR on firm value, with tax avoidance as a moderator. This study employs a quantitative approach and includes 32 manufacturing companies listed on IDX (128 observations), selected purposively. Secondary data from the companies' annual and sustainability reports are used in this research. This research is a panel data study utilizing data processing tools, namely STATA v.17. Data analysis was carried out using panel data regression with a moderation test. Findings reveal that intellectual capital and CSR significantly influence firm value, whereas capital structure shows no effect. Furthermore, the role of tax avoidance is shown to be ineffective in moderating the connection between intellectual capital, capital structure, and CSR with firm value. These results imply that during 2020-2023 period investor may have prioritized innovation, productivity, and corporate reputation over financing decisions, a condition that differs from earlier studies reporting a positive role of capital structure, The absence of moderating effect from tax avoidance may also reflect tighter tax regulations and growing investor awareness of good governance, making tax savings less attractive as a driver of firm value.